Finnar, tyskar och andra folkgrupper i Stockholms senmedeltida stadsböcker i ljuset av ursprungsangivelser - Ryman, Lennart (Nordic Journal of Socio-Onomastics, 2024)
This article confronts two methods of identifying individuals with reference to geography in a source from medieval Stockholm, Sweden: prepositional phrases with a place name as complement, such as Erich i Nyabode ‘Erik in Nyboda’ and appositions denoting origin, such as Peder Skaning ‘Peter Scanian’. A partly complementary pattern emerges where prepositional phrases are common for areas close to Stockholm, while corresponding appositions are rare; for distant areas, appositions tend to be more common and prepositional phrases rarer. There are two groups that do not follow this pattern: Finns and Germans. For Finns there are a relatively high number of prepositional phrases, while finne is a common apposition. For Germans, both appositions denoting origin and prepositional phrases are rare. A common trait is that both Finnish and German origin can be stated for women and for anonymous people, which is otherwise rare. These patterns may be explained by Germans constituting both an in-group in the city and a foreign group from a general Swedish perspective, whereas Finns were both compatriots and considered somewhat foreign.